Let { a n } be a recurrent sequence such that a 1 = 1 and a n = ⌊ a 1 + a 2 + ⋯ + a n − 1 ⌋ for all n > 1 . Find a 1 0 0 0 .
Notation:
⌊
⋅
⌋
denotes the
floor function
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How do you prove that all of the powers of 2 appear 3 times?
@Andrew Hucek , umis cesky? muj tatinek je z ceska tak ja umim mluvit cesky
The regularity is obvious.But I persuade myself to treat this problem rigorously.
Let’s show that
a
2
k
+
k
−
1
=
a
2
k
+
k
=
a
2
k
+
k
+
1
=
2
k
−
1
,
a
2
k
+
k
+
1
+
2
j
−
1
=
a
2
k
+
k
+
1
+
2
j
=
2
k
−
1
+
j
,
for all
k
≥
2
and
1
≤
j
≤
2
k
−
1
−
1
.........(#)
Do induction on k . For k = 2 ,we have a 5 = a 6 = a 7 = 2 , a 8 = a 9 = 3 .
Assume that we now have (#) for the cases 2 , … , k ( k ≥ 2 ) ,then we get
i = 1 ∑ 2 k + 1 + k + 1 − 2 a i = 1 + 2 i = 1 ∑ 2 k − 1 i + i = 0 ∑ k − 1 2 i = 1 + 2 k ( 2 k − 1 ) + ( 2 k − 1 ) = 2 2 k .
And so a 2 k + 1 + k + 1 − 1 = ⌊ i = 1 ∑ 2 k + 1 + k + 1 − 2 a i ⌋ = ⌊ 2 2 k ⌋ = 2 k .
It leads to the result a 2 k + 1 + k + 1 = ⌊ 2 2 k + 2 k ⌋ = 2 k , and a 2 k + 1 + k + 1 + 1 = ⌊ 2 2 k + 2 k + 2 k ⌋ = 2 k ,
since ⌊ 2 2 k + 2 k ⌋ = 2 k ⟺ 2 k ≤ 2 2 k + 2 k < 2 k + 1 ⟺ 2 2 k ≤ 2 2 k + 2 k < 2 2 k + 2 ⋅ 2 k + 1 holds true evidently and the latter can be obtained in the same way.
__Using this method,we can obtain several similar equalities (they're colored in blue and you can check them on your own) .
Then do induction on j in the case k + 1 .
it's easy to check the case when j = 1 :
a ( 2 k + 1 + k + 1 + 1 ) + 1 = ⌊ 2 2 k + 2 k + 2 k + 2 k ⌋ = 2 k + 1 , and a ( 2 k + 1 + k + 1 + 1 ) + 2 = ⌊ 2 2 k + 2 k + 2 k + 2 k + ( 2 k + 1 ) ⌋ = 2 k + 1 .
Assume that we have showed the cases 1 , . . . , j ( j ≥ 1 ) ,then we got
a ( 2 k + 1 + k + 1 + 1 ) + 2 j + 1 = ⌊ 2 2 k + 2 k + 2 k + 2 k + i = 1 ∑ j ( a ( 2 k + 1 + k + 1 + 1 ) + 2 i − 1 + a ( 2 k + 1 + k + 1 + 1 ) + 2 i ) ⌋
= ⌊ 2 2 k + 3 ⋅ 2 k + 2 i = 1 ∑ j ( 2 k + i ) ⌋ = ⌊ 2 2 k + 3 ⋅ 2 k + j ⋅ 2 k + 1 + j ( j + 1 ) ⌋ = 2 k + j + 1 .
and we can get a ( 2 k + 1 + k + 1 + 1 ) + 2 j + 2 = 2 k + j + 1 in the same way.
So we've finished the proof.In fact, using the proved results we can culculate every term in the sequence separately .
So a 1 0 0 0 = a 2 9 + 9 + 1 + 2 ⋅ 2 3 9 = 2 8 + 2 3 9 = 4 9 5 .
Problem Loading...
Note Loading...
Set Loading...
If we write down some of the first numbers, we get: ( 1 , 1 , 1 , 1 , 2 , 2 , 2 , 3 , 3 , 4 , 4 , 4 , 5 , 5 , 6 , 6 , 7 , 7 , 8 , 8 , 8 , 9 , 9 , … ) . From this it is visible that number 1 appears four times, while all other numbers appear twice, thrice at most. We will further define that numbers that appear thrice are the powers of 2 , starting with 2 1 . All other numbers therefore appear twice.
Suppose we wrote down the beginning of the sequence until the first occurrence of the number n ( n > 1 ) . And that the sequence visibly behaves as defined.
Let k be the largest integer satisfying 2 k < n . Then the sum of all the values is:
s 1 = ( 1 + 2 + . . . + n ) + ( 1 + 2 + . . . + n − 1 ) + ( 1 + 2 + 2 2 + . . . + 2 k ) + 1 = n 2 + 2 k + 1 .
Because 2 k + 1 = 2 × 2 k < 2 n < 2 n + 1 = ( n + 1 ) 2 − n 2 . . Whe have s 1 < ( n + 1 ) 2 and the following member is therefore ⌊ s 1 ⌋ = n .
Now we define the next member in this order, we see that the sum is now: s 2 = s 1 + n = n 2 + n + 2 k + 1 , so if 2 k + 1 < n + 1 , then s 2 < ( n + 1 ) 2 and the next member is n .
However k is the largest integer satisfying 2 k < n , so its true that n ≤ 2 k + 1 . The previous situation therefore occurs iff 2 k + 1 = n .
When n isn't a power of two, the next member is n + 1 , because n + 1 ≤ 2 k + 1 < 2 n < 3 n + 4 , because ( n + 1 ) 2 ≤ n 2 + n + 2 k + 1 < ( n + 2 ) 2 .
Now it is only needed to show, that if n = 2 k + 1 , then after three occurences of n , a n + 1 will follow.
So now the sum is:
s 3 = s 2 + n = n 2 + 2 n + 2 k + 1 = n 2 + 3 n , and we immediately get the inequality ( n + 1 ) 2 < s 3 < ( n + 2 ) 2 .
Now we finally see that 5 0 0 = a 1 0 1 0 = a 1 0 0 9 , from where we finish a 1 0 0 0 = 4 9 5 .